Efeito da exposição à atrazina nas brânquias de curimbatá, Prochilodus lineatus (Teleósteo, Prochilodontidae) - Paulino, Marcelo Gustavo (2011)
The herbicide atrazine is one of the most common pesticides found in the aquatic ecosystems all over the world. In this study the effects of atrazine, at sublethal concentrations, were evaluated on the gills of Prochilodus lineatus. Juveniles P. lineatus were divided in 4 groups: control and exposed to atrazine (2, 10 e 25 μg.L-1) for 48 hours or 14 days. After the experimental periods, blood samples were taken by caudal puncture for ion plasma analusis and the gills were removed and samples were fixed for morphological analysis (chloride cell immunohistochemistry, scanning electron microscopy, histochemistry of mucous cells and histopathology) or frozen for biochemical analysis (Na+/K+-ATPase and oxidative stress enzyme activity, GSH and determination of lipid hydroperoxidation). The activity of antioxidant enzymes (SOD, CAT e GST) e lipid peroxidation increased in fish of group exposed to 10 μg.L-1 for 14 days. Although there was an increase on plasma Na+ e Cl- and osmolality in fish exposed for 14 days it was not characterized as ionic imbalance as the Na+/Cl- ratio was similar in all groups. The total number of chloride cells decreased significantly only in the group exposed to 25 μg.l-1 of atrazine (48 h) and the CC density at epithelial surface and the fractional surface area of chloride cells increase in both treatments (48 h and 14 days) in fish exposed to 25 and 10 μg.l-1, respectively. The Na+/K+-ATPase activity was not altered in any experimental condition. The number of mucous cells containing sulfated mucins decreased. Hypertrophy and disruption of lamellar epithelium and vascular congestion were the most common injuries found in the gill tissue of P. lineatus and in fish exposed to 25 μg.l-1 atrazine (14 dias) the histopathological changes index was calculate as slightly to moderate. In conclusion, the tested concentrations, which are similar to those found in natural environments, may cause alterations in the gills of P. lienatus, so as not to endanger the vital functions of the gills and homeostasis of the animal. The changes observed in the gill of P. lineatus after atrazine exposure at tested concentrations, similar to that found in the natural environment, suggested that atrazine may affect the organ function.